Pola pertumbuhan rumput laut (Eucheuma cottonii) yang menggunakan kantong dan tanpa kantong di perairan pantai Geger, Nusa Dua, Bali - Loka, Made Tri; Dewi, Ayu Putu Wiweka Krisna; Wijayanti, Ni Putu Putri (Jurnal Biologi Udayana, 2023)
This research was conducted to determine the growth pattern of seaweed (Eucheuma cottonii) using bags and without bags in Geger beach in October-November 2022. The data collection of this study was carried out once a week for six weeks. The cultivation method used in this study was the off-bottom method with bag and bagless treatment (conventional). This study was designed using a completely randomized design (CRD). To find out SGR data (weight growth rate per day) can be analyzed using the One Way Anova test, with a significant level of 5% from the results of the analysis, which is 95%. The statistical test was assisted by using SPSS PC software. Var 25.0. The results of this study indicate that the growth of seaweed when using bags was higher than without bags. The weight of seaweed when using the bags in the 6th week was 666 g and without the bags in the 6th week was only 375 g. The Specific Growth Rate (SGR) for the use of bags was 5.53%/day and the treatment without bags was 2.12%/day. This happened because the seaweed was broken by the currents and eaten by predators in the bagless treatment. Water quality parameters measured during the study yielded a range suitable for seaweed growth, namely, temperature 26.7-30ºC, salinity 31-35 ppt, pH 7.1-8.0, DO 5.9-6.7 mg /l, nitrate 0.034-0.057 mg/l, phosphate 0.011-0.066 mg/l, current speed 0.31-0.50 m/s and brightness 60-107 cm. The measurement values of nitrate and phosphate in Geger Beach waters were low however it can still support seaweed cultivation activities. Seaweed growth with bag use was better than without bag with a weight difference of 291 g at the end of the study. This result is in the good category in seaweed cultivation.